1982
DOI: 10.1007/bf02535092
|View full text |Cite
|
Sign up to set email alerts
|

Effects of zinc deficiency and castration on fatty acid composition and desaturation in rats

Abstract: The effects of zinc deficiency and testosterone on fatty acid composition of plasma lipids and microsomes of liver, intestine and testes were studied. The activities of fatty acid desaturase (delta 6 and delta 5) in rat liver and testes were also measured. A significant decrease in the level of arachidonic acid was observed in plasma of normal rats fed the zinc-deficient diet. Castration significantly decreased arachidonic acid but increased 20:3 fatty acid, which is negligible in normal rats. Testosterone and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
31
1
2

Year Published

1985
1985
2011
2011

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(37 citation statements)
references
References 16 publications
3
31
1
2
Order By: Relevance
“…In support of this suggestion is the very stable repartition in the phospholipids between endogenous (saturated and mono-unsaturated fatty acids) and exogenous fatty acids (n-6 and n-3 families) shown in Tables 3 to 5. These results agree with those of Clejan et al [4].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In support of this suggestion is the very stable repartition in the phospholipids between endogenous (saturated and mono-unsaturated fatty acids) and exogenous fatty acids (n-6 and n-3 families) shown in Tables 3 to 5. These results agree with those of Clejan et al [4].…”
Section: Discussionsupporting
confidence: 94%
“…is required for the activity of 46 desaturase, a microsomal enzyme that converts linoleic acid into gamma-linolenic acid and that it may be one of the important factors in the cause of essential fatty acid deficiency [4].…”
mentioning
confidence: 99%
“…Desaturase activities could also be affected in diabetes mellitus and be dependent on insulin (el Boustani et al, 1989). Furthermore, it has been suggested that zinc and selenium could play a role in the desaturation of n-3 and n-6 polyunsaturated fatty acids (Clejan et al, 1982;Infante, 1986;Celik et al, 1999). To this end, we have already shown (Quilliot et al, 2001) that the plasma zinc concentration was below normal in chronic pancreatitis patients, and that plasma selenium concentra-tions were lower in chronic pancreatitis patients than in healthy controls.…”
Section: Introductionmentioning
confidence: 86%
“…The physicochemical and transport properties of both the brush border and basolateral membranes can vary with fatty acyl chain composition, cholesterol and phospholipid head group content [9,11]. In turn, these components, and hence structural and metabolic activities of enterocytes, can be influenced by fasting and dietary manipulation [9,10,[12][13][14][15]. While there has been interest in the possible interaction of vitamin A status and membranes for many years [16][17][18][19], and young rats given large doses of vitamin A have been found to have greater total intestinal lipid content and monoglycerides than controls [20,21], we are not aware of any studies conducted to investigate intestinal epithelial lipid composition in vitamin A deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Although no studies have examined the effect of protein energy malnutrition on intestinal fatty acid profile, malnourished rabbits have an altered intestinal microvillous membrane lipid composition [13], and short-term fasting in rats has been found to modify the fatty acid profile of intestinal microsomes [12]. Furthermore, by feeding the same diet to all groups of rats, we have also controlled for the effects of any other nutrients which may influence intestinal mucosal fatty acid composition [9,10,12,14,15].…”
Section: Discussionmentioning
confidence: 99%